Design of experiment in practice: formulation design and optimization of sustained release tablet dosage form of Ketorolac - Khan, Tanisha Tabassum Sayka (BRAC University, 2016)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016